2010
DOI: 10.1088/0964-1726/19/3/035018
|View full text |Cite
|
Sign up to set email alerts
|

Selective Lamb mode excitation by piezoelectric coaxial ring actuators

Abstract: The article describes an omni-directional multi-element transducer for selective Lamb wave mode excitation. It is composed of several coaxial ring-shaped piezoelectric elements actuated by n-cycled sinusoidal tonebursts. Mode selection is achieved by a special choice of the time delays and the amplitudes of the input driving signals. The method for the determination of these parameters is based on strict analytical considerations. In the limiting case of the infinite number of cycles and with a sufficient numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…These arrangements will be referred to as "active-center" and "inactive-center" geometries, respectively. Thus the 0 th -order Hankel transform of the inactive-center geometry function of the N-ring annular array is given in equation (12). It can also be shown that for the case of the active-center annular array, the Hankel transform is that given in equation (13).…”
Section: Wavenumber-domain Excitation Spectrum By Spatial Fourier Tramentioning
confidence: 99%
See 1 more Smart Citation
“…These arrangements will be referred to as "active-center" and "inactive-center" geometries, respectively. Thus the 0 th -order Hankel transform of the inactive-center geometry function of the N-ring annular array is given in equation (12). It can also be shown that for the case of the active-center annular array, the Hankel transform is that given in equation (13).…”
Section: Wavenumber-domain Excitation Spectrum By Spatial Fourier Tramentioning
confidence: 99%
“…Guided wave excitations of the CLoVERs have been studied by them as well. Selective guided wave excitations using annular array patches were recently studied by Glushkov et al, [12]. An optimization approach was developed to maximize the energy ratio of the selected wave mode to the total guided wave excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Phase delays, Δ = Δ + Δ are applied to the ℎ and ℎ elements along the x, y directions. Thus, the actuating function for such a phased array with 2 × 2 elements can be mathematically expressed in the spatial and temporal domains as: where, ( ) is the boxcar function which has magnitude of unity within an area 4 and zero elsewhere and f(t) is the input voltage applied to the element at the origin. The Fourier domain representation of Eq.…”
Section: D Linear Patmentioning
confidence: 99%
“…In [3] 1D phased array transducers are considered and time delays for guided wave mode control is presented. In [4] time delays and variable amplitudes are applied to individual elements of an annular array for selective generation of guided waves in plates. Use of circularly arranged annular phased array transducers are suggested for both mode control and steering [5].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent work on curved segmented IDTs has been carried out by Salas and Cesnik 17 who applied a 2D spatial Fourier transform to the wave equation and loading distribution; mode control was not attempted by means of specifying the IDT spacing but by utilizing IDT segments that were split at a given radius, allowing the activation of curved segmented IDTs with either a predetermined smaller or larger radius to preferentially excite and receive particular wave modes. Glushkov et al 18 utilized a Fourier transform of the wave equation to achieve selective Lamb wave mode excitation by varying time delays and amplitudes among the elements of a bonded annular array applying radial shear loading at the element edges; however, no mention is made of optimizing the geometric parameters of the annular array.…”
Section: Introductionmentioning
confidence: 99%